Teachers’ perception towards islamic methods of finance / Rozita Ibrahim - Ibrahim, Rozita (2013)
Islamic banking products and services are gaining popularity among people across the globe due to its wider product coverage and ability to traverse the global economic melt-down. However, to what extent this statement is true in Malaysian context. Hence, this research aims to examine teachers’ perception towards Islamic Methods of finance in Malaysia. The analysis of this research involved 100 respondents, all of whom are based in Pasir Mas, Kelantan. The result of the study showed that Islamic banking services are not making headway among people in Kelantan. Despite this negative trend, more efforts need to be energized to enhance the level of understanding for customers on the Islamic banking concepts. Similarly, a more comprehensive research is required to be undertaken to uncover various reasons of Islamic banking selection by teachers. For the degree of perception, the link between principles, differences and selection criteria could not be established with the perception that the establishment of Islamic banking will improve the overall banking facilities since most of the respondents were unsure of Islamic banking products and services are gaining popularity among people. Several analysis including, frequency analysis, reliability analysis, regression analysis including F-test and ANOVA were used to evaluate all these factors. Thus, an appropriate means of investigating the topic from this perspective was done through data collection of questionnaires to understand the meanings they have for their response and expectations. Results have clearly shown that there is a no significant result between the teachers’ perception towards Islamic methods of finance and principles, differences and selection criteria of Islamic banking. Recommendations are being suggested to propose the best ways for public to increase and upgrade their understanding in the future